1999
DOI: 10.1007/s004649901055
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on heat production by a 23.5-kHz ultrasonically activated device for endoscopic surgery

Abstract: An experimental study was carried out to evaluate heat production by an ultrasonically activated device (USAD) using an animal model. In an anesthetized living pig, the gastroepiploic and mesenteric vessels were coagulated and cut by an USAD at a power level of 70% (n = 8) or 100% (n = 8). During the division, the time-discrete temperature change on the surface of the animal tissue adjacent to the blade was measured by thermography. To compare the USAD with conventional electrocautery (EC), a full-thickness in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 7 publications
1
46
0
Order By: Relevance
“…Real-time thermography studies have shown that the level of collateral heat spread was higher than that observed in histological studies [3]. It was also demonstrated that the ultrasonic scalpel induced a lateral spread of heat into contiguous tissue conducting to a temperature higher than 60°C, up to 10 mm around the electrode [12]. The laparoscopic ultrasonic coagulating shears was found to provoke a mean lateral thermal injury of 1.6 mm [8], and the heat spread with standard bipolar electrocautery can be as large as 22 mm [12].…”
Section: Discussionmentioning
confidence: 96%
“…Real-time thermography studies have shown that the level of collateral heat spread was higher than that observed in histological studies [3]. It was also demonstrated that the ultrasonic scalpel induced a lateral spread of heat into contiguous tissue conducting to a temperature higher than 60°C, up to 10 mm around the electrode [12]. The laparoscopic ultrasonic coagulating shears was found to provoke a mean lateral thermal injury of 1.6 mm [8], and the heat spread with standard bipolar electrocautery can be as large as 22 mm [12].…”
Section: Discussionmentioning
confidence: 96%
“…Although there is no definite data in the literature, nevertheless there are clear evidences that ultrasonic energy decreases lateral thermal damage and creates lower temperatures than electrosurgery with potentially lower risk of inadvertent injuries to surrounding structures. Besides, the necrotic tissue associated with electric surgical char may compromise healing, whilst carbonisation in surrounding tissues with ultrasonic dissection is minimal compared to both unipolar and bipolar coagulation [22][23][24][25][26]. In one randomised study, the perforation rate during laparoscopic cholecystectomy was significantly lower with US than with electrocautery [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the assumption that the described devices significantly reduce the risk of collateral thermal injury was disproved by animal experimentation, which confirmed the Graphic 2 LigaSure versus ultracision energy: operating time generation of very high temperatures at the instrument tip and thermal damage [11,[27][28][29]. Among the alternative energy sources, an innovation in tissue-selective separation/dissection using water jet could be the Erbejet 2 (ERBE USA, Inc., Georgia), which uses precise and gentle pressure rather than intense heat.…”
Section: Discussionmentioning
confidence: 69%